Characteristics of the leg extensors in male volleyball players with jumper's knee - Lian, O.; Engebretsen, L.; Ovrebo, R. V.; Bahr, R. (The American Journal of Sports Medicine, 1996)
The aim of the present study was to characterize the performance ability of the leg extensor apparatus in a group of athletes with jumper's knee and to compare the results with those of a matched control group without knee symptoms. Patient and control groups (12 players in each) were selected from a population of 141 well-trained male Norwegian volleyball players, of which 55 (39%) satisfied the diagnostic criteria for jumper's knee. The testing program consisted of a standing jump, a countermovement jump, a 15-second rebound jump test, a standing jump with a 20-kg load, and a standing jump with a load corresponding to one-half of the subject's body weight. Jump height and power were measured using a contact mat connected to an electronic timer. The test results of the patient group were significantly higher than those of the control group for the countermovement jump (15% increase), power during rebound jump (41%), work done in standing jump (12%) and countermovement jump (22%), and the difference between countermovement jump and standing jump (effect of adding eccentric component). Athletes with jumper's knee demonstrated better performance in jump tests than uninjured athletes, particularly in ballistic jumps involving eccentric force generation.